Impactos socioambientais decorrentes do rompimento da barragem de Fundão no município de Barra Longa, Minas Gerais - Teresa Cristina Guerra de Andrade (2018)
The landscape reflects the relationship between human beings and the environment in face of different transformations occurring over time. Mining activities, due to their extracting nature, produce significant transformations in the landscape. In mining, risks and impacts related to waste dams are among the most important. Disasters related to dam rupture are related to civil works and labeled as technological ones. On November 5th, 2015, a dam belonging to the company Samarco Mineração, associated to BHP Billiton, An Anglo-Australian conglomerate, and its Brazilian counterpart Vale S.A., broke in Mariana, Minas Gerais (Brazil). That disaster caused nineteen deaths and important environmental impact on the region, destroying Bento Rodrigues, a sub-district of the municipality of Mariana, affecting several towns and cities. Barra Longa was one of the sites affected by the rupture of the dam, as well as its district of Gesteira. The disaster caused significant environmental impact, alteration of the landscape, contamination of Carmo and Gualaxo Rivers, altering the way of life of the local population and damaging material cultural heritage. This paper aims to identify the effects of the rupture of the Fundão waste dam on the surrounding landscape. Its case study deals with the mentioned disaster in the municipality of Barra Longa, Minas Gerais. Discussions on the importance of promoting sustainable development, considering the environmental, economic, social and cultural dimensions, are part of the approach. We intend to provide subsidies for research and the development of public policies towards risk disaster management.